Corpus size - Sardinha, Tony Berber (The ESPecialist, 2012)
This paper addresses the question of determining the typical size of corpora used in research reported in Corpus Linguistics conferences and meetings. By surveying the corpora actually used by corpus linguistics in their research projects over a period of several years, it was possible to calculate the range of variation in corpus size in the field and estimate levels of acceptability held by the community. This approach contrasts with subjective views put forth by Corpus Linguistics practitioners on the issue of corpus size.